Assessment of tumor margins in head and neck cancer using a 3D-navigation system based on PET/CT image-fusion – A pilot study. Issue 4 (April 2018) - Zrnc, Tomislav A.; Wallner, Jürgen; Zemann, Wolfgang; Pau, Mauro; Gstettner, Christian; Brcic, Luka; Assaf, Alexandre T.; Hassanzadeh, Hamid; Feichtinger, Matthias; Schwenzer-Zimmerer, Katja
Abstract: Objectives: Determination of tumor margins in patients with squamous cell carcinoma of the head and neck (SCCHN) is mostly based on preoperative magnetic resonance imaging (MRI) or computed tomography scans (CT). Local recurrence of disease is often correlated with the presence of positive resection margins after surgical treatment. Positron emission tomography/computed tomography (PET/CT) imaging plays a crucial role in the assessment of patients with SCCHN. The purpose of this study was to determine whether PET/CT could predict tumor extension. Methods: In 12 patients who underwent surgical treatment of primary SCCHN (Stage III-IV) F18-FDG PET/CT image-fusion was performed on a 3D navigation-system based workstation. Image-guided needle biopsies were obtained from four different, color-coded metabolic areas within the tumor. The histopathological findings were correlated with findings on corresponding PET/CT scans. Results: 81.3% of biopsies from the central area were positive. Specimens taken from the outer metabolic zone were positive in 66.7% of the patients. The highest incidence of positive biopsies was found in the zone adjacent to the outermost area. There was a statistically significant difference in positive tumor histopathology when comparing the various metabolic zones (p = 0.03). Conclusion: Exact determination of tumor is an important research topic, although results remain controversial. The results of this study suggest that in some cases PET scans may overestimate tumor extension.